Interação assíncrona entre professores e coordenação: espaço on-line para formação em serviço - Breda, Luciana (2007)
This study aims at 1) describing and interpreting the asynchronous on-line interaction among coordinators and teachers, taken as a phenomenon of human experience, and 2) investigating representations of teachers and coordinators concerning face-to-face pedagogical reunions, their roles and responsibilities. These goals intend to collect subsidies that allow the forthcoming building of an asynchronous interaction area restricted to teachers and coordinators to complement the live pedagogical reunions. To achieve these purposes, this study is founded on the social-cultural approach to teaching and learning (Vygotsky, 1978/2006, 1934/2003 and 1934/2003), on the notion of representations proposed by Freire and Lessa (2003), and on studies about on-line interaction (Andrade & Vicari, 2003, Lamy & Goodfellow, 1999, Almeida, 2003, Hanna, Glowacki-Dudka & Conceição-Runlee, 2000 and Parreiras, 2001). The methodological approach chosen is the hermeneutical-phenomenological one (Ricoeur, 1986/2002;van Manen, 1900). The research context is a bilingual pre-school located in the southern part of the city of São Paulo and the participants are its three coordinators and seven teachers. Taking into consideration the methodological approach selected and the description and interpretation of the phenomenon on focus, this study aims at identifying: 1) representations teachers and coordinators have of the pedagogical reunions; 2) representations teachers and coordinators have of their roles, and 3) the nature of on-line interaction between teachers and coordinators is. The data were collected thru two questionnaires sent to teachers and coordinators, respectively, and thru two hundred and thirty-four e-mail messages. The results indicate that teachers and coordinators have a very similar comprehension about what a pedagogical reunion is. Therefore, regarding roles and responsibilities, their representations are not always coincident. As for the phenomenon in focus, it is possible to understand that it brings a structure in which the participants pursue a necessity of interaction and action, which is complementary to the necessity of diversity of subjects and roles